Preoperative CT-Guided Near-Infrared Dye Marking for Thoracoscopic Resection of Pulmonary Nodules: A Case Report - Voulaz, Emanuele; Testori, Alberto; D'Antuono, Felice; Cariboni, Umberto; Alloisio, Marco; Mangiameli, Giuseppe (Frontiers in Surgery, 2022)
Localization of small-sized pulmonary nodules is challenging during video-assisted thoracoscopic surgery (VATS). Several preoperative strategies have been developed to mark these targets. We describe our localization strategy using a preoperative computed tomography (CT)-guided near-infrared dye marking.